Rejecting Sectarianism: Palestinian Christians' Role in Muslim-Christian Relations - Haiduc-Dale, Noah (Islam and Christian-Muslim relations, 2015)
The study of Muslim-Christian relations often focuses on Islamic theology and Muslim behavior while overlooking the role that Christians play in shaping interreligious encounters. This article examines a series of historical examples from various periods of Palestinian history that highlight Arab Christians' insistence that they were Palestinian Arabs first and were fully engaged in the nationalist movement. Palestinian Christians' approach to local politics, even in the face of interreligious conflict, allowed them to maintain far better relations with Muslims than Arab Christians in some neighboring Arab countries. By way of comparison, the article highlights the Druze's acceptance of a unique communal relationship to the Zionist leadership and later, to the state of Israel. The article concludes that, while modern Islamism presents a challenge to minority Christian groups, historical examples suggest that Christians' actions have a profound impact on the nature of Christian-Muslim relations.